Using Project-Based Learning Model with Mind Mapping Method to Increase Students' Learning Motivation - Aprilia Rizqina Nuramalina; Hafnati Rahmatan; Rini Safitri; Andi Ulfa Tenri Pada; Cut Nurmaliah; Evendi Evendi (Jurnal Penelitian Pendidikan IPA, 2022)
Students' motivation in learning are still low in the subjects of Craft and Entrepreneurship. Therefore, a project-based learning model is needed that is able to increase students' motivation in learning. This study aims to determine the effect of the project-based learning model with mind mapping method in increasing learning motivation of students in the subjects of Craft and Entrepreneurship. The research design used was a one group pretest-posttest design. The population in this study were all students of class X SMA Negeri 1 Meulaboh as many as 254 students. The number of samples amounted to 48 students. Learning motivation data were analyzed by comparing the scores of learning motivation before and after the implementation of project-based learning in the experimental class which was tested for significance through the Wilcoxon average difference test. The results showed that the learning motivation of students before and after the application of the learning model had a significant difference (p value = 0.00; p < 0.05). The conclusion of this study is that there are differences in students' learning motivation before and after the application of the project-based learning model